Mutation of H-ras is infrequent in bladder cancer : confirmation by single-strand conformation polymorphism analysis, designed restriction fragment length polymorphisms, and direct sequencing - KNOWLES, M. A; WILLIAMSON, M (Cancer research (Chicago, Ill.), 1993)
A series of 152 human bladder tumors, 14 bladder tumor cell lines, and 1 immortal urothelial cell line were examined by single-strand conformation polymorphism (SSCP) and designed restriction fragment.length polymorphism analyses for mutations in exons 1 and 2 of the H-ras gene. Nine tumors (6%) contained mutations. There was complete concordance between SSCP and restriction fragment length polymorphism analyses. Six mutations in exon 1 and three in exon 2 were identified by SSCP analysis. Subsequent restriction fragment length polymorphism analysis showed that of the exon 1 mutations, four were in codon 12 and two in codon 13, and all three exon 2 mutations were in codon 61. Eight mutations were confirmed by direct sequencing. One codon 13 mutation could not be identified by direct sequencing. Distinct strand mobility shifts detected by SSCP analysis identified specific point mutations, and in all cases, strands containing different mutations migrated differently. The base substitutions identified in these bladder tumors were diverse and included four transversions (three G-->T and one A-->T) and four transitions (two G-->A and two A-->G). This pattern of base substitutions is compatible with interactions of the urothelium with more than one class of environmental agent during bladder tumor development. No correlation was found between tumor grade and/or stage and the presence of H-ras mutation. We conclude that H-ras mutation does not play a role in the development of the majority of transitional cell tumors of the bladder.